Pengalihan Hak Atas Tagihan Atas Nama atau Cessie yang Berkepastian Hukum - Lemta , Benjamin; Iryani, Dewi; Aji , Puguh (Sekolah Tinggi Ilmu Hukum (STIH) Prof Gayus Lumbuun, 2024)
Debt and credit transactions are common occurrences in business activities. Often, debtors are unable or have not yet fulfilled their obligations, while creditors need immediate funds even before the due date of their receivables. In such cases, Civil Law provides a solution through the institution of